Analysis of teaching at the right level assessment in sixth grade elementary school students - Triwahyuningtyas, Dyah; Suastika, I Ketut; Sesanti, Nyamik Rahayu; Muhammad, Azamul Fadhly Noor (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze the implementation of a Teaching at the Right Level (TaRL) assessment through differentiated student worksheets and its effect on student motivation and understanding. Using a descriptive qualitative method, the research involved 28 sixth-grade students in Malang City. Data were collected via observation, interviews, document analysis, and student reflections. The main findings indicate that the TaRL-based assessment significantly enhanced student engagement and motivation in learning. By accommodating students’ differing developmental stages—’beginning to develop,’ ’developing,’ and ’proficient’—teachers could provide more targeted instruction. Students reported feeling more confident and challenged, while teachers found classroom management more effective, despite challenges related to the extra time and effort required to create differentiated materials. Overall, the study concludes that the TaRL approach is effective in creating a positive and productive learning environment. The practical implications suggest a need for teacher training in designing valid diagnostic assessments and for developing a system of flexible student worksheets to reduce their workload. This would support the implementation of a student-centered approach and enhance the quality of inclusive education.